Developmental outcomes of 3, 4‐methylenedioxymethamphetamine (ecstasy)‐exposed infants in the UK. (July 2015) - Singer, Lynn T.; Moore, Derek G.; Min, Meeyoung O.; Goodwin, Julia; Turner, John J. D.; Fulton, Sarah; Parrott, Andrew C.
<x xml:space="preserve">Abstract</x> Objective This paper aims to review findings from a longitudinal study of prenatal methylenedioxymethamphetamine (MDMA, "ecstasy") on infant development. Methods In a prospective, longitudinal cohort design, we followed 28 MDMA‐exposed and 68 non‐MDMA‐exposed infants from birth to 2 years of age. Women recruited voluntarily into a study of recreational drug use during pregnancy were interviewed to obtain type, frequency, and amount of recreational drug use. Their children were followed for a 2‐year period after birth. A large number of drug and environmental covariates were controlled. Infants were seen at 1, 4, 12, 18, and 24 months using standardized normative tests of mental and motor development. Results There were no differences between MDMA‐exposed and non‐MDMA‐exposed infants at birth except that MDMA‐exposed infants were more likely to be male. Motor delays were evident in MDMA infants at each age and amount of MDMA exposure predicted motor deficits at 12 months in a dose‐dependent fashion. Conclusions Prenatal MDMA exposure is related to fine and gross motor delays in the first 2 years of life. Follow‐up studies are needed to determine long‐term effects. Copyright © 2015 John Wiley & Sons, Ltd.